Characterization and Antibiotic Sensitivity Profile of Bacteria Isolated from Patients with Respiratory Tract Infections in Bangladesh (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The study was aimed to characterize bacterial isolates from respiratory tract infections (RTI) and   investigate their antibiotic sensitivity profile. Selective media and biochemical tests were used to characterize 40   bacterial isolates. Antibiotic sensitivity testing was conducted using Kirby-Bauer disc diffusion method. About   42.5% (17) RTI patients were infected by Klebsiella pneumoniae, 30% (12) by Escherichia coli and 27.5% (11) by   Pseudomonas aeruginosa with no significant gender variation (p-value